b - Mark , Woolfson lisa; Boyle, J. (b, 2017)
This textbook is a detailed yet accessible overview of modern professional approaches to educational psychology. Ranging from well-established, popular methods to emerging, innovative theories, the book covers a broad span of frameworks, and considers how they meet the complex criteria challenging professionals in the field today.
Includes bibliographical references and index
Keywords: Educational psychology -- Textbooks